Characterization of plasma rotating electrode atomized Nb-Ti based alloy powder. Issue 2 (March 2020) - Li, Qijun; Zhang, Lin; Chen, Xiaowei; Wei, Dongbin; Zhang, Peng; Chen, Yan; Qu, Xuanhui
Abstract : Nb-Ti based alloy powder was prepared by plasma rotating electrode process. The relationship between microstructure, particle size and cooling rate was investigated. Phase constituents and surface state of the powder were characterized. The results indicated that particle size of the Nb-Ti based alloy powder ranged from 30 to 165 μm. Most of the atomized Nb-Ti based alloy powder particles had a smooth surface and near-perfect spherical shape. The atomized powder was found to be single β phase with dendritic, cellular or microcrystalline structure. The reduction in powder size and the increase in cooling rate had transformed the solidification morphologies of the PREP powder from dendrite in major to a cellular structure. The secondary dendritic spacing was measured to be 1.32 ∼ 2.71 μm, and the corresponding cooling rates were estimated to be in the range of 4.50 × 10 4 ∼ 3.75 × 10 5 K·s −1 . Oxygen contamination on the surface of the powder existed in the form of Nb2 O5 and TiO2, and the thickness of the oxide layer was about 8 nm.